Students' use of the young adult collection at the Immaculate Conception Cathedral School High School Library - Sta. Ana, Ann Marie C.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2009)
One of the most important duties of a school library and media center is to make resources and services accessible and available to its users. Aside from its main function which is to support the curriculum of the school, it has many other secondary functions such as stimulating the imagination of children, promoting critical thinking, exposing children to diverse points of view, and providing entertaining diversions (Rubin, 2000). These functions are fulfilled by the library by promoting and encouraging students to read; more specifically recreational or voluntary reading.
Sadly, children and young adults nowadays have so many other things that keep them busy. There's the television, computers and the Internet. One of the great tragedies of the computer age is that less and less people go to the library and read, even for leisure. This is why libraries and librarians are constantly challenged to instill in the youth a desire to read.
The young adult collection consists of fiction, nonfiction, magazines, newspapers, comic books, and audio-visual materials (Nichols, 2002). Young adult literature has gone through a transformation in the last 40 years. Before, it was used only as supportive reading but now it has become a rich literary source that meets the abilities of all types of readers. It offers contemporary themes and exposes readers to societal problems that young people can relate to which in turn serves as a guide for them when they find themselves in similar situation in the future.
This study sought to find the use patterns of books from the Young Adult collection at the Immaculate Conception Cathedral School-High School Library, the students' reading interests and their opinions regarding the library's collection. The descriptive survey method was used for the study, which involves a survey questionnaire, along with information from book cards. The respondents were high school students from first through fourth year. Data were tabulated and analyzed using frequency counts, percentages and rankings. Chi-square test of independence was used for find out if a relationship exists between the variables.
Findings show that more than half of the sample (61) use the Young Adult collection of their library, and their favorite type of material are magazines, fiction and nonfiction. The book that was being used by the most number of students was the World Almanac, followed by Nancy Drew/Hardy Boys, and the Adventures of Tom Sawyer, Reading interests for fiction reveal that the respondents prefer in order: horror, mystery, and adventure, while for nonfiction, the respondents' favored history, art, animals, and sports.
The respondents were mostly satisfied with their library's Young Adult collection especially with the theme or subject content of materials but were mostly dissatisfied with the library as a whole. Data analysis reveals that the various factors influencing the respondents' use of the Young Adult collection such as age, gender, economic status, and family background do not have a significant relationship with the respondents' frequency of use and number of hours spent per day in using the library's materials for leisure, or with the type of material that they use.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Immaculate Conception Cathedral School High School Library; Young adult literature